Natural products for glycaemic control: Polyphenols as inhibitors of alpha-amylase. (September 2019) - Sun, Lijun; Warren, Fredrick J.; Gidley, Michael J.
Abstract: Background: α-Amylase plays an important role in starch digestion, the main source of exogenous glucose in the human diet. Retarding glucose absorption through delaying digestion of starchy foods by inhibiting α-amylase in the digestive tract has potential as a management and/or therapeutic approach to type II diabetes. Polyphenols have been reported to have inhibitory activity against the enzyme. Scope and approach: This review provides an overview of structure-activity relationships of dietary polyphenols inhibiting α-amylase and the underlying mechanisms. The methods applied to characterize binding interactions between polyphenols and α-amylase, as well as the relationships between the constants obtained from these methods are discussed. As polyphenols can interact with both polysaccharides and α-amylase, the potential effects of polysaccharides on the binding of polyphenols with α-amylase are also summarised. Key findings and conclusions: The inhibition of α-amylase by polyphenols results from binding interactions between the enzyme and polyphenols. The galloyl moiety in polyphenols plays an important role. IC50, inhibition kinetics, fluorescence quenching, differential scanning calorimetry, isothermal titration calorimetry and molecular docking can be comprehensively combined to analyze the binding interactions, as the constants obtained from these methods can be correlated. Soluble polysaccharides may reduce the binding and inhibitory action of polyphenols against α-amylase. Most work reported in this review is from in vitro studies, so if and how the binding interactions affect starch digestion in vivo need to be further studied. Highlights: Inhibition of α-amylase by polyphenols results from molecular binding interactions. The galloyl moiety in polyphenols plays an important role in binding. Calorimetry, fluorescence quenching, molecular modelling and kinetic analysis combined. Soluble polysaccharides reduce amylase binding and inhibition action of polyphenols. Most insights from in vitro studies, more in vivo studies needed.